Perlindungan Hukum Terhadap Pihak Ketiga dalam Penyelesaian Pembagian Harta Waris Islam: Analisis Peran dan Tanggung Jawab Notaris - Dinda Amarthya Rachmadhany (Journal of Creative Student Research, 2026)
The distribution of Islamic inheritance documented in a notarial deed has legal implications not only for heirs but also for third parties who possess legal interests in the deceased’s estate. Third parties, such as creditors and bona fide purchasers, are often in a vulnerable position when inheritance distribution is conducted without considering attached legal rights. This study aims to analyze the forms of legal protection for third parties and the role and responsibility of notaries in ensuring legal certainty in Islamic inheritance distribution. This research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that notarial deeds function as both preventive and repressive legal protection instruments and position notaries as key actors in safeguarding justice, legal certainty, and the protection of third-party rights within Islamic inheritance law.